Can public participation in haze governance be guided by government？ --Evidence from large-scale social media content data mining. (10th October 2021) - Xu, Shuling; Sun, Kaining; Yang, Binbin; Zhao, Li; Wang, Bo; Zhao, Wenhui; Wang, Zhaohua; Su, Minli
Abstract: It has been proved that top-down governance alone has limitations in the process of air pollution control, and public participation plays an important role in promoting air pollution governance. However, whether the public awareness of participating in haze governance can be guided by government and the guiding mechanism are still unclear. This paper is based on data from a leading Chinese social media—— Sina Weibo . Over 10.54 million haze-related blogs from 2013 to 2017 have been excavated. Based on the latent Dirichlet allocation (LDA) topic model, the characteristics and evolutionary path of the government and public concern have been analyzed. Furthermore, the empirical results indicate the following. (1) The government has a significant role in promoting the public concern about participating in haze governance. (2) Regional heterogeneity, especially regions with underdeveloped economies, low levels of education and aging populations should receive special attention. (3) The effect of the government is not all-round, "haze governance" and "public participation" have significant impacts on the public concern regarding "participating in haze governance". (4) Media and government have a reciprocal relationship in terms of attracting public attention to haze governance. They are vying for people's limited attention. (5) There are spatial spillover effects of local government. Finally, policy implications and the fairness of online promotion and reflection on the public are discussed.